Determinants of Public Intention to Participate in Digital Waqf Using the Theory of Planned Behavior with Trust in the Indonesian Waqf Board as a Moderating Variable - Tanjung, Ayu Wulandari S.; Nasution, Yenni Samri Juliati; Syahriza, Rahmi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study investigates the determinants of public intention to participate in digital waqf through the lens of the Theory of Planned Behavior (TPB), with trust in the Indonesian Waqf Board (BWI) serving as a moderating variable. The analysis explores four key factors: attitude, subjective norms, perceived behavioral control, and trust in digital waqf management institutions. A quantitative approach employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied. Data were collected via questionnaires distributed to 200 Muslim respondents in North Sumatra Province. The findings indicate that attitude, subjective norms, perceived behavioral control, and trust significantly and positively influence the intention to engage in digital waqf. Moreover, trust was found to moderate the relationships between attitude and intention, as well as perceived behavioral control and intention, but not between subjective norms and intention. These results underscore the pivotal role of trust, alongside psychological factors, in strengthening public willingness to contribute to digital waqf. The study’s implications highlight the need to enhance digital waqf literacy, ensure transparent governance, and reinforce BWI’s role in fostering public trust. Such measures are expected to boost community participation in digital waqf, particularly in North Sumatra, thereby advancing Islamic philanthropy and the Islamic economy in Indonesia.